Teaching speaking : (Cambridge University Press, 2012)
This book provides theoretical and pedagogical perspectives on teaching speaking within a coherent methodological framework. Teaching Speaking A Holistic Approach brings together theoretical and pedagogical perspectives on teaching speaking within a coherent methodological framework. The framework combines understandings derived from several areas of speaking research and instruction. By explaining, interpreting, evaluating, and synthesizing these diverse perspectives from linguistics and language learning, the text offers a comprehensive and versatile approach for teaching speaking. Different types of learning tasks are explained and illustrated with examples, and each chapter includes short tasks and ends with a number of tasks that enable readers to extend their ideas